Self-regulated learning and students with disabilities: a mini review - Aydan, Seda; Mamas, Christoforos (Frontiers in Education, 2025)
Self-Regulated Learning (SRL) has been extensively cited in research as a process enabling students to develop cognitive, behavioral, and emotional strategies to achieve academic success. However, while SRL has been widely studied in typically developing student populations, its role in supporting students with disabilities remains largely underexplored. This mini literature review synthesizes existing SRL research tailored for students with disabilities in K-12 education. The review highlights the challenges these students face in areas such as reading, writing, and mathematics, emphasizing the importance of metacognitive awareness, self-efficacy, and strategic learning behaviors. It further investigates how SRL interventions, such as Self-Regulated Strategy Development (SRSD) and structured cognitive modeling, can enrich academic performance and motivation. Findings have also revealed that students with disabilities are often presented with limited opportunities to develop SRL skills systematically, indicating a need for more inclusive and adaptive instructional strategies. By synthesizing research and emerging perspectives, this review offers insights into effective SRL interventions and calls for further research to fill in existing gaps, ultimately creating a more supportive learning environment for students with disabilities.